Pengaruh Religiusitas Terhadap Loyalitas Nasabah - Sahputra, Julfan; Harahap, Rijal Allamah (Peduli Riset dan Pengabdian Masyarakat, 2022)
The source of this research data was obtained from the answers to the questionnaire given to the customers of PT. Bank Syariah Indonesia (BSI) Tbk Sub-Branch of Pangkalan Brandan. Processing and analysis of data in this study using the computer program SPSS 22.00 and Microsoft Office Excel. The results showed that there was a significant influence between religiosity on customer loyalty at BSI Tbk Sub Branch Pangkalan Brandan. This is evidenced by the statistical results showing that religiosity (X) statistically shows a significant value less than 0.05 or (0.00 < 0.05) and the tcount > ttable (14.730 > 1.98447). The religiosity of PT. BSI Tbk Pangkalan Brandan Sub-Branch affects their loyalty to continue using the products and services offered by BSI Tbk Pangkalan Brandan Sub-Branch by 68.6%, while the remaining 31.4% (100% - 68.6%) is influenced by the following variables: another variable. The positive coefficient means that there is a positive relationship between religiosity and customer loyalty, the higher the level of religiosity of PT. BSI Tbk Pangkalan Brandan Sub Branch, the more loyal they are to continue to use the products and services offered by PT. BSI Tbk Sub-Branch of Pangkalan Brandan.